2007
DOI: 10.1161/circulationaha.106.669697
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection by Ecto-5′-Nucleotidase (CD73) and A 2B Adenosine Receptors

Abstract: Background— Ecto-5′-nucleotidase (CD73)–dependent adenosine generation has been implicated in tissue protection during acute injury. Once generated, adenosine can activate cell-surface adenosine receptors (A 1 AR, A 2A AR, A 2B AR, A 3 AR). In the present study, we define the contribution of adenosine to cardioprotection by ischemic preconditioning. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
558
3
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 405 publications
(591 citation statements)
references
References 36 publications
28
558
3
2
Order By: Relevance
“…Previous studies from our group and others found that A 2B AR was up-regulated in ischemic mouse hearts [16,17]. A 2B AR has recently been shown to have cardio-protective properties [18,19] However, A 2B AR-mediated CF regulation under ischemic conditions has not been studied. A comparative study of cardiac ischemia-reperfusion in A2AWT and A2AKO may give us more information about the role of A 2B AR in CF regulation under ischemia, i.e.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous studies from our group and others found that A 2B AR was up-regulated in ischemic mouse hearts [16,17]. A 2B AR has recently been shown to have cardio-protective properties [18,19] However, A 2B AR-mediated CF regulation under ischemic conditions has not been studied. A comparative study of cardiac ischemia-reperfusion in A2AWT and A2AKO may give us more information about the role of A 2B AR in CF regulation under ischemia, i.e.…”
Section: Discussionmentioning
confidence: 94%
“…EC 50 values for BAY 60-6583 are 3-10 nM for human A 2B and >10 µM for A 1 and A 2A ARs [18,19]. Protocol for constructing the concentration-response relationship to BAY 60-6583 was the same as for L-NAME concentration-response curves, except the concentration range is from 10 −11 to 10 −5 M.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ ischaemic pre-conditioning conferred cardioprotection in A1R, A2AR and A3R, but not A2BR knockout mice, or in wild-type mice after inhibition of A2BR, and thus, it was suggested that 5′-nucleotidase and A2BR agonists might be considered as therapeutic agents for myocardial ischaemia [554,555]. Activation of A3R protected against myocardial ischaemia-reperfusion injury in mice, an effect which disappeared in A3R knockout mice [529,556,557].…”
Section: Ischaemiamentioning
confidence: 99%
“…Although the lymph was derived from patients with different underlying morbidities, these data thus collectively suggest that the intralymphatic lymphocytes can produce substantial levels of anti-inflammatory adenosine when they are exiting the tissues. CD73 regulates the permeability of blood vessels under inflammatory conditions [7,[11][12][13][14][15][16][17]30]. Thus, the blood vasculature of all studied organs in CD73-deficient mice has been shown to be leakier to small molecules in multiple models of ischemiareperfusion injury and LPS-induced inflammation when compared to WT mice.…”
mentioning
confidence: 99%